Architecture, playing and vanishing - María Berríos (Materia Arquitectura)
In this essay I will focus on an exceptional group of architects and poets who have explored vanishing as a form of action, by means of grandiloquent geo-poetic expeditions through more or less vast American territories, for over sixty years. I will try to imagine the formulation of an aesthetics of invisibility in which active vanishing operates like an emancipatory practice as a ludic proposal that challenges real sociopolitical and economic hierarchies and promotes new horizons for collective living. Even though when referring to the Escuela de Valparaíso, it might be more appropriate to think in terms not of aesthetics, but of poetics – in the sense of poiesis – whose radicality is in its concept of an architecture of living together, based on opening, risking and daring to expose one another, sometimes even to the extreme of vanishing.